Reference values for electrolytes and blood gases in Wistar rats with permanent cerebral ischemia: The effect of treatment with glycine on gasometry and electrolytes - Uribe Escamilla, Rebeca; Sánchez Aparicio, Pedro; Córdova Izquierdo, Alejandro; Alfaro Rodríguez, Alfonso (Multiciencias, 2012)
Cerebral ischemia is a common neurological condition in people with hypoxia. Glycine is an inhibitory neurotransmitter that could protect neurons from hypoxia-induced toxicity. The aim of this study was to obtain reference values on gasometry and electrolytes and evaluate the effect of treatment with glycine on gasometry and electrolytes in Wistar rats with ischemic brain injury. Fifteen male Wistar rats (mean body weight, 340 g) were randomly allocated to the following three groups: G0 rats underwent permanent left carotid occlusion and received treatment with a placebo; G1 rats underwent a permanent left carotid occlusion and received treatment with glycine i.p 40mMol/kg post-surgery; G2 rats with surgery received treatment with glycine i.p 40mMol/kg 5 days pre-surgery. Blood was obtained by cardiocentesis to determine reference values for electrolytes and blood gases. The results show some major alterations in acid base and electrolytes in G0, and statistical significance in glucose levels for G1,2. Glycine administered to Wistar rats with permanent left carotid occlusion limited changes in the acid base and electrolytes and increased glucose levels from the beginning of the ischemia, initiating brain protection by altering the cascade of events that lead to cellular death.